French repressive judiciary in Algeria during the period of military rule 1830-1870 - Ben Mabrouk, noui (The Algerian Historical Journal, 2026)
The French rule in Algeria during the military period (1830-1870) was marked by a systematic use of legal instruments to suppress and control the Algerian population. Through decrees, laws, and the collaboration of local leaders, the French administration sought to establish a firm grip on the territory and enforce its colonial agenda. This approach, driven by the interests of European settlers, led to widespread land dispossession, harshpunishments fordissenters, and the erosion of Algerian rights.